PENERAPAN KONSELING BEHAVIORAL DENGAN MEDIA VIDEO TERAPI UNTUK MENGATASI PERILAKU BOLOS SISWA KELAS XI SMA NEGERI 1 ABIANSEMAL TAHUN PELAJARAN 2018/2019 - Karpika, I Putu; Purnami, Kadek Ratih Sri (Widyadari: Jurnal Pendidikan, 2019)
Deviant behavior today is carried out by the young generation of the nation's successors, especially those related to disciplinary violations in schools, one of which is ditching. Truant behavior is actually not a new thing anymore for many students at least those who have been educated, because truant behavior itself has been around for a long time. The tail will indeed become a phenomenon that clearly tarnishes the educational institution itself. Not only in big cities, students who appear to be often absent, even in rural areas ditching has become an academic disease that needs serious treatment. The effort that has been made by BK teachers is to provide information services to students, apparently the information services provided are not very effective. It is evident that there are still many class XI students who play truant in Abiansemal 1 high school. Based on this description, researchers will use behavioral counseling with video therapy media to overcome truant behavior of students. The reason the researcher chose this counseling was that the researcher wanted to change the behavior of ditching class XI students.